An Analysis Of Grammatical Errors In Students' Descriptive Text Writing In Seventh Grade At SMP Negeri 3 Pematangsiantar - Dwi Angeli Pardede; Sanggam Siahaan; Tiarma Intan Marpaung (PIJAR: Jurnal Pendidikan dan Pengajaran, 2026)
This research aimed to analyze the types and factors of grammatical errors in descriptive texts written by seventh-grade students at SMP Negeri 3 Pematangsiantar. This research used a qualitative descriptive method. The data were collected from descriptive texts written by 30 students and analyzed using the Surface Strategy Taxonomy by Dulay et al. and the theory of error factors by Ellis. The findings showed that 105 grammatical errors were identified. Misformation was the most dominant error type (60%), followed by omission (33.3%) and addition (6.7%), while misordering was not found. In addition, intralingual transfer was the dominant contributing factor (67.6%), especially incomplete application of rules. These findings indicate that students’ grammatical errors were mainly caused by incomplete mastery of English grammar and the influence of their first language, Bahasa Indonesia.